Study of Release-Retardant Polymers in Formulation Development of Cinnarizine-HCl Sustained-release Oral Suspension Using Raft Technology: Study of Release-Retardant Polymers in Formulation - Islam, Tabinda; Hossain, Nusrat; Rahman, Mohsina; Shabnam, Sadia; Chowdhury, Eyasmin; Nahar, Syeda Tahsin; Gias, Zarin Tasnim; Reza, Hasan Mahmud (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The main objective of this research was to develop a sustained-release suspension of cinnarizine hydrochloride using raft-forming technique. This innovative approach has been utilized to formulate a series of suspension formulations using hydroxypropyl cellulose (HPC) as a release-retardant polymeric agent. Cinnarizine sustained-release suspensions were prepared by physical mixing method with varying concentrations and combinations of HPC, sodium citrate, sodium saccharin, calcium carbonate, sodium alginate, methyl hydroxybenzoate and propyl hydroxybenzoate. The formulations were subjected for determination of floating time, floating lag time, weight of the raft, physical appearance and in-vitro dissolution. The dissolution was conducted through USP apparatus 2 (paddle type) in 0.1N hydrochloric acid medium having pH 1.2. The key findings of the study demonstrate that a stable sustained-release suspension of cinnarizine can be formulated using raft-forming approach for increased bioavailability and patient-convenience. Dhaka Univ. J. Pharm. Sci. 19(1): 15-24, 2020 (June)